Free Riding in Loan Approvals : Evidence from SME Lending in Peru - Arraiz, Irani; Bruhn, Miriam; Roth, Benjamin N.; Ruiz-Ortega, Claudia; Stucchi, Rodolfo (World Bank, Washington, DC, 2019)
This paper provides evidence that commercial lenders in Peru free ride off their peers' screening efforts. Leveraging a discontinuity in the loan approval process of a large bank, the study finds that competing lenders responded to additional loan approvals by issuing approvals of their own. Competing lenders captured almost three-quarters of the new loans to previously financially excluded borrowers, greatly diminishing the profits accruing to the initiating bank. Lenders may therefore underinvest in screening new borrowers and expanding financial inclusion, as their competitors reap some of the benefit. The results highlight that information spillovers between lenders may operate outside credit registries.